2023
DOI: 10.1001/jamainternmed.2023.3562
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Aneurysm Repair Devices as a Use Case for Postmarketing Surveillance of Medical Devices

Xuan Wang,
Vidul Ayakulangara Panickan,
Tianrun Cai
et al.

Abstract: ImportanceThe US Food and Drug Administration (FDA) is building a national postmarketing surveillance system for medical devices, moving to a “total product life cycle” approach whereby more limited premarketing data are balanced with postmarketing surveillance to capture rare adverse events and long-term safety issues.ObjectiveTo assess the methodological requirements and feasibility of postmarketing device surveillance using endovascular aneurysm repair devices (EVARs), which have been the subject of safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Details of the missing rates for covariates and the method of multiple imputation are shown in Table S1 and Appendix S1. Adjusted absolute risk differences for 5 and 10 years based on the cumulative incidence information were used to summarize the association between PD and all-cause mortality (Elhence et al, 2023;Wang et al, 2023;Weinberg et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the missing rates for covariates and the method of multiple imputation are shown in Table S1 and Appendix S1. Adjusted absolute risk differences for 5 and 10 years based on the cumulative incidence information were used to summarize the association between PD and all-cause mortality (Elhence et al, 2023;Wang et al, 2023;Weinberg et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Using doubly robust estimation, Wang et al aimed to estimate average treatment effects (AFX device minus non-AFX devices) for type III endoleaks and all-cause mortality while protecting against model misspecification. Notably, this protection can extend to the proportional hazards assumption often made with Cox models by modeling baseline hazards stratified by treatment group .…”
Section: Description Of Doubly Robust Estimationmentioning
confidence: 99%
“…In the October 2023 issue of JAMA Internal Medicine , Wang et al used electronic health record data of 13 941 patients who had received an implanted endovascular aneurysm repair device (EVAR) to evaluate associations of specific devices with rates of type III endoleaks and all-cause mortality. The authors used doubly robust causal modeling to evaluate endovascular graft devices used to treat an abdominal aortic aneurysm (AAA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation by Wang and colleagues 6 comes on the heels of 2 recent studies evaluating the safety of AFX stent grafts. 7,8 Despite using methodologies with different data sources, patient populations, and analytical approaches, all 3 groups found that the AFX stent grafts were associated with higher safety risks than were other EVAR devices.…”
mentioning
confidence: 99%